Digital Map Based on Project Based Learning Material on Ethnic and Cultural Diversity in Indonesia - Ni Made Feby Trisna Dewi; Anak Agung Gede Agung; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2025)
Student learning outcomes in social studies frequently remain low because the material is perceived as difficult and dominated by memorization, resulting in limited conceptual understanding. Learning media that lack interactivity and contextual relevance also contribute to students’ low engagement during lessons. This study aims to analyze, develop, and evaluate the effectiveness of a Project-Based Learning–based digital map to enhance students’ understanding of ethnic and cultural diversity in Indonesia. This research employed the ADDIE development model, encompassing analysis, design, development, implementation, and evaluation stages. The subjects consisted of 25 grade V students, while the data were collected through tests and questionnaires using validated instruments. Data analysis involved descriptive quantitative techniques and an inferential paired-sample t-test to determine the effectiveness of the developed media. The findings conceptually indicate that the digital map supports deeper learning by helping students construct knowledge through exploration and problem-solving activities embedded in project-based learning tasks. The study concludes that a digital map designed through a PjBL approach can effectively improve conceptual mastery of ethnic and cultural diversity while fostering student engagement. This research implies that technology-based learning media should be increasingly integrated into instructional practices to support interactive, student-centered learning.